Risk factors associated with preterm birth in singletons born after IVF: a national cohort study. Issue 4 (April 2023) - Gervoise-Boyer, Marie-Josée; Fauque, Patricia; De Mouzon, Jacques; Devaux, Aviva; Epelboin, Sylvie; Levy, Rachel; Valentin, Morgane; Viot, Géraldine; Bonomini, Justine; Bergère, Marianne; Jonveaux, Philippe; Pessione, Fabienne
Abstract: Research question: What are the risk factors for prematurity other than intrauterine growth restriction in singletons after IVF? Design: Data were collected from a national registry, based on an observational prospective cohort of 30, 737 live births after assisted reproductive technology (fresh embryo transfers: n = 20, 932 and frozen embryo transfer [FET] n = 9805) between 2014 and 2015. A population of not-small for gestational age singletons conceived after fresh embryo transfers and FET, and their parents, was selected. Data on a number of variables were collected, including type of infertility, number of oocytes retrieved and vanishing twins. Results: Preterm birth occurred in 7.7% ( n = 1607) of fresh embryo transfers and 6.2% ( n = 611) of frozen–thawed embryo transfers ( P < 0.0001; adjusted odds ratio [aOR] = 1.34 [1.21–1.49]). Endometriosis and vanishing twin increased the risk of preterm birth after fresh embryo transfer ( P < 0.001; aOR 1.32 and 1.78, respectively). Polycystic ovaries or more than 20 oocytes retrieved also increased preterm birth risk (aOR 1.31 and 1.30; P = 0.003 and P = 0.02, respectively); large oocyte cohort (>20) was no longer associated with the risk of prematurity in FET. Conclusion: Endometriosis remains a risk for prematurity even in the absence of intrauterine growth retardation, which suggests a dysimmune effect. Large oocyte cohorts obtained by stimulation, without clinical polycystic ovary syndrome diagnosed before attempts, do not affect FET outcomes, reinforcing the idea of a phenotypic difference in the clinical presentation of polycystic ovary syndrome.